1994
DOI: 10.2307/2061755
|View full text |Cite
|
Sign up to set email alerts
|

Nativity Concentration and Internal Migration among the Foreign-Born

Abstract: Are immigrants who live in states where large numbers of their compatriots reside more or less likely to migrate than those who live in other states? Using 1980 U.S. Census data to address that question, the analysis shows that nativity concentration deters interstate migration but not migration within the same state. Residing in a state where fellow nationals live is a more important determinant of internal migration than human capital, immigration status, or a state's unemployment rate. New York State reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
191
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(204 citation statements)
references
References 29 publications
11
191
0
2
Order By: Relevance
“…Foreign-born concentration at destination is a strongly significant attractor of internal migration, both absolutely and relative to origin generation. While foreign-born concentration has often been seen to deter outmigration (see for example Bartel andKoch 1991, Kritz andNogle 1994), it is a hallmark of spatial assimilation conceptions that concentration should diminish as an attractor over time (and by extension, intergenerationally). In these models of destination choice, estimated for those who are already migrants, destination concentration is a significant determinant of where to move.…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign-born concentration at destination is a strongly significant attractor of internal migration, both absolutely and relative to origin generation. While foreign-born concentration has often been seen to deter outmigration (see for example Bartel andKoch 1991, Kritz andNogle 1994), it is a hallmark of spatial assimilation conceptions that concentration should diminish as an attractor over time (and by extension, intergenerationally). In these models of destination choice, estimated for those who are already migrants, destination concentration is a significant determinant of where to move.…”
Section: Model Resultsmentioning
confidence: 99%
“…Put simply, there is significant investment in the idea that immigrants will disperse from concentrated immigrant cities through internal migration, and that dispersal is part and parcel of the way in which immigrant incorporation takes place (Bartel 1989, Kritz andNogle 1994). Although the evidence on this theory is mixed, it is not too early to consider the internal migration patterns of the rapidly growing second generation population.…”
Section: Introductionmentioning
confidence: 99%
“…To model the probability of living in a gateway city (the fi rst outcome), there are numerous studies that identify the determinants of city choice which can be used here to provide guidance (Lieberson and Waters, 1987;Bartel, 1989;Kritz and Nogel, 1994;Newbold, 1996;Zavodny, 1999;McDonald, 2003;Aslund, 2005;Cebula, 2005;Scott et al, 2005 …”
Section: The Analytical Modelmentioning
confidence: 99%
“…Examples for the Spanish case include works by authors such as Malheiros (2002), Arbaci (2004), Bayona (2007), Fullaondo (2003), Fullaondo and Roca (2007), Checa and Arjona (2006) and Leal (2007). Studies on the United States include Kritz and Nogle (1994), who examine the concentration of immigrants in metropolitan areas and argue that migratory movements tend to favor ethnic grouping. It has also been shown that the origin of migration flows determines immigrants' preferences for settling in rural or urban environments (Fullaondo and Roca 2007).…”
Section: Introductionmentioning
confidence: 99%